Predictors and survival of cardiomyopathy determined by echocardiography in Thai patients with early systemic sclerosis: an inception cohort study - Suparaporn Wangkaew; Narawudt Prasertwitayakij; Jirapath Intum; Juntima Euathrongchit (Scientific Reports, 2023)
Abstract Available data including the incidence, predictors and long-term outcome of early systemic sclerosis patients associated with suspected cardiomyopathy(SSc-CM) is limited. Therefore, we aimed to study the incidence, predictors and survival of SSc-CM. An inception cohort study was conducted for early SSc patients seen at the Rheumatology Clinic, Maharaj Nakorn Chiang Mai Hospital, Thailand, from January 2010 to December 2019. All patients were determined for clinical manifestations and underwent echocardiography and HRCT at enrollment and then annually. SSc-CM was determined and classified using echocardiography. 135 early SSc patients (82 female,108 DcSSc) were enrolled. With the mean follow-up period of 6.4 years, 32 patients developed SSc-CM. The incidence of SSc-CM was 5.3 per 100-person years. The multivariate Cox regression analysis showed that baseline anti-topoisomerase I-positive (Hazard ratio[HR] 4.86, p = 0.036), dysphagia (HR 3.35, p = 0.001), CK level ≥ 500 U/L(HR 2.27, p = 0.045) and low oxygen saturation (HR 0.82, p = 0.005) were predictors of SSc-CM. The survival rates after SSc-CM diagnosis at 1, 5 and 10 years were 90.3%, 73.1%, and 56.1%, respectively. In this study cohort, the incidence of SSc-CM was 5.3 per 100-person years, and tended to have low survival. The presence of anti-topoisomerase I antibody, dysphagia, CK level ≥ 500 U/L, and low oxygen saturation were independent baseline predictors for developing SSc-CM.